Barriers in Healthcare to the Use of Optical Coherence Tomography Angiography in Multiple Sclerosis - Lukas G. Reeß; Hadi Salih; Murat Delikaya; Friedemann Paul; Frederike Cosima Oertel (Neurology and Therapy)
Abstract Optical coherence tomography angiography (OCT-A) is a state-of-the-art imaging technique for the retinal vasculature to accurately segment the capillary network and assign it to retinal layers. OCT-A is a promising technique to better understand neurological diseases with visual system manifestations, such as multiple sclerosis (MS), and to identify and characterize vascular biomarkers. Initial studies suggested vascular changes in MS and its differential diagnoses such as myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) and neuromyelitis optica spectrum disorder (NMOSD). Here we review clinical and technical aspects of OCT-A imaging and discuss the potential for the MS field as well as barriers that need to be overcome before OCT-A can be established in clinical application.